2021
DOI: 10.3390/v13061100
|View full text |Cite
|
Sign up to set email alerts
|

Human Astrovirus Outbreak in a Daycare Center and Propagation among Household Contacts

Abstract: We investigated an outbreak of acute gastroenteritis due to human astrovirus in a daycare center, describing the transmission mechanism, the most affected age groups, conditioning factors and the extent of the outbreak among household contacts of the daycare center attenders. Data were collected from persons exposed at the daycare center and their home contacts. Fecal samples from affected and non-affected daycare center attenders were analyzed for viruses causing acute gastroenteritis by RT-PCR. The percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Astroviruses are spread worldwide, and they are accountable for 2-9% of acute, nonbacterial diarrheal illnesses in children, even though their occurrence in clinical specimens was higher and reached 61% in symptomatic and asymptomatic individuals [116,118,121]. In other works, it was found that human astrovirus causes 10% of acute gastroenteritis sporadic cases in children of <3 y, and that most outbreaks occurred mainly in healthcare and daycare centers, while in some developing countries, infection rates reached 20% [117]. The symptoms of gastrointestinal tract and inflammatory lesions affecting the meninges and brain tissue as encephalitis and meningitis were also reported [122,123].…”
Section: Astrovirusmentioning
confidence: 95%
See 1 more Smart Citation
“…Astroviruses are spread worldwide, and they are accountable for 2-9% of acute, nonbacterial diarrheal illnesses in children, even though their occurrence in clinical specimens was higher and reached 61% in symptomatic and asymptomatic individuals [116,118,121]. In other works, it was found that human astrovirus causes 10% of acute gastroenteritis sporadic cases in children of <3 y, and that most outbreaks occurred mainly in healthcare and daycare centers, while in some developing countries, infection rates reached 20% [117]. The symptoms of gastrointestinal tract and inflammatory lesions affecting the meninges and brain tissue as encephalitis and meningitis were also reported [122,123].…”
Section: Astrovirusmentioning
confidence: 95%
“…Further, individuals infected with one strain do not acquire immunity against other strains. Globally, human astrovirus-1 and MLB-1 were the predominant genotypes detected in gastrointestinal tract infections [116][117][118][119]. Additionally, the most frequent viral co-infections reported with astrovirus illness involved norovirus and rotaviruses [120].…”
Section: Astrovirusmentioning
confidence: 99%